Factors Influencing the Degradation of Archival Formalin-Fixed Paraffin-Embedded Tissue Sections - Xie, Ran (SAGE Publications, 2011)
The loss of antigenicity in archival formalin-fixed paraffin-embedded (FFPE) tissue sections negatively affects both diagnostic histopathology and advanced molecular studies. The mechanisms underlying antigenicity loss in FFPE tissues remain unclear. The authors hypothesize that water is a crucial contributor to protein degradation and decrement of immunoreactivity in FFPE tissues. To test their hypothesis, they examined fixation time, processing time, and humidity of storage environment on protein integrity and antigenicity by immunohistochemistry, Western blotting, and protein extraction. This study revealed that inadequate tissue processing, resulting in retention of endogenous water in tissue sections, results in antigen degradation. Exposure to high humidity during storage results in significant protein degradation and reduced immunoreactivity, and the effects of storage humidity are temperature dependent. Slides stored under vacuum with desiccant do not protect against the effects of residual water from inadequate tissue processing. These results support that the presence of water, both endogenously and exogenously, plays a central role in antigenicity loss. Optimal tissue processing is essential. The parameters of optimal storage of unstained slides remain to be defined, as they are directly affected by preanalytic variables. Nevertheless, minimization of exposure to water is required for antigen preservation in FFPE tissue sections. This article contains online supplemental material at http://www.jhc.org. Please visit this article online to view these materials.